Influences of water velocity on ovarian maturation and antioxidant capacity in adult grass carp (Ctenopharyngodon idellus) - Shu, Tingting; Yang, Jing; Yu, Zhaoxi; Xiao, Kan; Huang, Hongtao; Dai, Lingquan; Yin, Zhan; Jiang, Wei (Frontiers in Marine Science, 2024)
Ecological operation of hydraulic engineering is essential for the conservation of fishery resources. Water velocity is known to affect the spawning of fishes delivering drifting eggs. This study aims to explore the effects of water velocity stimulation on the ovarian maturation and antioxidant capacity of adult grass carp (Ctenopharyngodon idellus) through laboratory experiments in order to understand the physiological mechanism underlying the response of natural reproduction to ecological flows. We examined the histology, sex hormones and vitellogenin (VTG) concentrations of ovary, and the transcripts of key genes in the hypothalamus-pituitary-gonad (HPG) axis, as well as the antioxidant activities of ovary and liver in grass carp. The results showed that although there was no discernible difference on the ovarian development characteristics of grass carp under water velocity stimulation, estradiol, testosterone, progesterone, 17α,20β-dihydroxy-4-pregnen-3-one (17α,20β-DHP), and VTG concentrations were elevated, which was related to the transcriptional regulation of the HPG axis genes. The gene expression levels (gnrh2, fshβ, lhβ, cgα, hsd20b, hsd17b3, and vtg) in the HPG axis were significantly elevated under water velocity stimulation, while those of hsd3b1, cyp17a1, cyp19a1a, hsd17b1, star, and igf3 were suppressed. In addition, appropriate water velocity stimulation could enhance body health status by increasing the activities of antioxidant enzymes in the ovary and liver. The results of this study provide the fundamental knowledge and data support for ecological operation of hydropower projects and river ecological restoration.